1999
DOI: 10.1073/pnas.96.13.7128
|View full text |Cite
|
Sign up to set email alerts
|

Permanence of brain sex differences and structural plasticity of the adult brain

Abstract: Sex differences in brain structure have been widely recognized since the pioneering studies of Raisman and Field (1). For the most part, brain sex differences are thought to arise in perinatal development through the actions of testosterone secreted by the developing testes, and these sex differences are believed to persist in the absence of gonadal hormones in adult life, very much like the basic plan of the male and female reproductive tracts, which are also developmentally determined. As shown in Fig. 1, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 44 publications
1
42
0
4
Order By: Relevance
“…Developmental origins of sex differences. The failure of estradiol to induce hippocampal spine formation and up-regulate transmission in the septo-hippocampal cholinergic projections in the male brain is dependent on the aromatization of testosterone and estradiol exposure in the neonatal period (Luine et al, 1986;McEwen, 1999;Mitsushima et al, 2009a). This is evidence that masculinization of the hippocampus occurs in much the same way as the hypothalamus, and predicts that responsiveness to estrogen will be suppressed in adulthood.…”
Section: B Preclinical Studiesmentioning
confidence: 67%
See 2 more Smart Citations
“…Developmental origins of sex differences. The failure of estradiol to induce hippocampal spine formation and up-regulate transmission in the septo-hippocampal cholinergic projections in the male brain is dependent on the aromatization of testosterone and estradiol exposure in the neonatal period (Luine et al, 1986;McEwen, 1999;Mitsushima et al, 2009a). This is evidence that masculinization of the hippocampus occurs in much the same way as the hypothalamus, and predicts that responsiveness to estrogen will be suppressed in adulthood.…”
Section: B Preclinical Studiesmentioning
confidence: 67%
“…Relatively few studies have made direct comparisons of males and females, but in some tests of hippocampal spatial discrimination (the Morris watermaze), hormone treatment of gonadectomized mice revealed that estradiol selectively impaired performance in females but had no effect in males (Fugger et al, 1998). Several reports suggest that functional sex differences are related to organizational influences in early development (Roof, 1993a,b;McEwen, 1999;. For example, exposure to high levels of estradiol during development improves (masculinizes) spatial behavior in adult female rats to levels seen in normal males (Williams and Meck, 1991).…”
Section: B Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, global variables such as these do not explain the regionally specific sex-related phenomenon noted in the present work. Hormonal effects (e.g., estrogen), operating both during brain development (40) and acutely (41), are known to have regional specificity (42), making them potential contributors to the differences observed. Given the discovery nature of the present work and the lack of prior coordination among centers, the specific sex differences that we observed should be interpreted with caution until replicated in an independent sample.…”
Section: Resultsmentioning
confidence: 99%
“…Circulating hormones also play a significant role in structural remodeling of the undamaged adult brain, as exemplified by androgen induced synaptic remodeling of the spinal cord (Rand and Breedlove 1995), ovarian hormone-induced synapse turnover in hippocampus (Yankova et al 2001), and stress-induced remodeling of dendrites in hippocampus (Magarinos et al 1996). Even some sex specific changes in neuronal structure and connectivity may be the product of hormone actions in adult life, rather than solely due to early developmental influences (Cooke et al 1999;McEwen 1999).…”
Section: Bruce S Mcewen Phdmentioning
confidence: 99%